Universalitas Persaudaraan Islam: Studi Kritik Hadis dengan Metode Takhrij dan Syarah - Reika Astri Nuraziza; Dadang Darmawan; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about brotherhood. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about brotherhood, in the narration of Bukhari no. 2262. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Bukhari no. 2262 is relevant to be used as a motivation for the development of universal Islamic brotherhood.